2021
DOI: 10.3390/jcm10040605
|View full text |Cite
|
Sign up to set email alerts
|

COVID-19 in Autoinflammatory Diseases with Immunosuppressive Treatment

Abstract: COVID-19 disease increases interleukin (IL)-1β release. Anti-IL-1-treatment is effective in IL-1-mediated autoinflammatory diseases (AID). This case series presents COVID-19 in patients with IL-1-mediated and unclassified AID with immunosuppressive therapy (IT). Patient 1 is a 34-year-old woman with an unclassified AID and methotrexate. Patients 2 and 3 (14-year-old girl and 12-year-old boy, respectively) have a Cryopyrin-Associated Periodic Syndrome (NLRP3 p.Q703K heterozygous, CAPS) treated with canakinumab … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
29
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 16 publications
(29 citation statements)
references
References 50 publications
0
29
0
Order By: Relevance
“…In addition, superficial administration of vaccines more likely causes local side effects. 3 Obese individuals are at greater risk for severe SARS-CoV-2 infection and seem to generate poorer humoral vaccination responses compared with normal-weight persons. 4 Therefore, correct administration of SARS-CoV-2 vaccines is essential in the obese population.…”
Section: Conflict Of Interestmentioning
confidence: 99%
See 1 more Smart Citation
“…In addition, superficial administration of vaccines more likely causes local side effects. 3 Obese individuals are at greater risk for severe SARS-CoV-2 infection and seem to generate poorer humoral vaccination responses compared with normal-weight persons. 4 Therefore, correct administration of SARS-CoV-2 vaccines is essential in the obese population.…”
Section: Conflict Of Interestmentioning
confidence: 99%
“…After the launch of vaccination campaign, several new potential adverse events have been reported both with BNT162b2 mRNA and ChAdOx1 adenovirus vaccine. In particular, BNT162b2 mRNA vaccine has been associated both with symptomatic and asymptomatic thrombocytopenia, 3 while ChAdOx1 with several cases of a new, life-threatening, thrombotic thrombocytopenic disease resembling the heparin-induced thrombocytopenia, for which the new term vaccine-induced thrombocytopenic thrombosis (VITT) has been proposed. 4 Besides, in severe cases of COVID-19 microthrombotic phenomenon is considered at the basis of the multiorgan microangiopathy associated with the SARS-CoV-2 infection, so that heparin is now one of the cornerstones of severe COVID-19 treatment.…”
mentioning
confidence: 99%
“…There is definitely a role of immunosuppression in treating Post COVID-19 patients with ocular hyperinflammatory status. [ 9 10 ]…”
mentioning
confidence: 99%
“…To support these conclusions, indeed, it is notable that AIFA (Italian Medicines Agency) has recently authorized anakinra, an anti-IL-1β drug (already used for rheumatoid arthritis) for the treatment of patients affected by COVID-19, and other studies confirmed the efficacy of biologic drugs for the early comparison to COVID-19 clinical manifestation [ 199 , 200 , 201 ].…”
Section: Discussionmentioning
confidence: 99%